Temperature regulation in animals - Koirala, Ram Prasad (BIBECHANA, 2010)
We have studied the rate of evaporation of sweat for the body of human of two different surface areas at different temperatures. We have also studied the rate of evaporation of sweat at different values of heat produced by chemical metabolism. It is found that a thin man perspires at lower temperature than a fat man when they both produce the same heat by chemical metabolism. Keywords: Chemical metabolism; Evaporation of sweat; Normal breathing DOI: 10.3126/bibechana.v7i0.4037 BIBECHANA 7 (2011) 14-17